The Attitudes of Teachers towards 2005 Academic Year Primary Education Program - Dogan, Suleyman (EDAM, 2010)
This study is considered to be significant in objectively analyzing the negative-positive effects of the program during the process of learning, teacher's acquaintance to the new program in a closer way and acquiring a positive perspective of the program. This study has been conducted in order to discover the effects of 2005-2006 academic year primary education program on cognitive-emotional-psychomotor acquisitions, and expectations of the students in learning process. The sampling of the research consisted of 836 teachers (Women: 438, Men: 397) of state and private primary education institutions selected by random sampling method in Istanbul in 2008-2009 academic year. Research data were collected by the Scale of Teachers' Attitude towards New Primary Education Program consisted of 27 questions developed by the researcher. This study aims objectively at designating the negative-positive effects of the program during the process of learning. Moreover, perceptions and attitudes of primary education teachers towards the 2005 academic year primary education program are studied; the relationship between the previous and the new program is tried to be designated; and the differences and limitations of the new program are also discovered. Hence, the study aims at contributing to the concerned officials and researchers. The attitudes of the teachers towards the new educational program do not show significant differences in respect to gender, experiences, educational levels and state of graduation. However, there is a significant difference of their perspectives about new educational program in respect to their marital status and the institutions they work at. The results of the study were compared and discussed with several former program evaluation examples.
Keywords: Teacher; Teaching; Program; Primary Education Program; Teacher Attitudes; Education & Educational Research